Meloidogyne incognita Fatty Acid- and Retinol- Binding Protein (Mi-FAR-1) Affects Nematode Infection of Plant Roots and the Attachment of Pasteuria penetrans Endospores - Phani, Victor; Shivakumara, Tagginahalli N.; Davies, Keith G.; Rao, Uma (Frontiers in Microbiology, 2017)
Root-knot nematode (RKN) Meloidogyne incognita is an economically important pest of crops. Pasteuria penetrans, is a nematode hyperparasitic bacterium capable of suppressing the reproduction of RKN and thereby useful for its management. Secreted fatty acid and retinol-binding (FAR) proteins are unique in nematodes and are engaged in nutrient acquisition, development and reproduction; they are also a component of the nematode cuticle and thought to be involved in the interface between hosts and parasites. Attachment of endospores to the cuticle of second stage juveniles of RKN is the primary step of infection and several factors have been identified to facilitate attachment. In this study, the full length of Mi-far-1 (573 bp) was cloned from M. incognita and characterized. Analysis revealed that the Mi-far-1 was rich in α-helix structure, contained a predicted consensus casein kinase II phosphorylation site and a glycosylation site. Quantitative PCR (qPCR) showed the highest expression in the fourth stage juveniles and in situ hybridization revealed the presence of Mi-far-1 mRNA in the hypodermis below the cuticle. Single copy insertion pattern of Mi-far-1 in M. incognita genome was detected by Southern blotting. Knockdown of Mi-far-1 showed significantly increased attachment of P. penetrans’ endospores on juvenile cuticle surface and also affected host finding, root infection and nematode fecundity.